Domestic and Multilateral Effects of Capital Controls in Emerging Markets - Gurnain Pasricha; Matteo Falagiarda; Martin Bijsterbosch; Joshua Aizenman (Bank of Canada, 2015)
Using a novel data set on capital control actions in 17 emerging-market economies (EMEs) over the period 2001 - 11, we provide new evidence on domestic and multilateral (or spillover) effects of capital controls. Our results, based on panel vector autoregressions, suggest that capital control actions had limited impact on the variables of the monetary policy trilemma, as a result of offsetting resident flows and ample investment opportunities in EMEs. These findings highlight the importance of the macroeconomic context and of the increasing role of resident flows in understanding the effectiveness of capital inflow management. Tightening of capital inflow restrictions in Brazil, Russia, India, China and South Africa (the BRICS) generated significant spillovers via bank lending and exchange rates, particularly in the post-2008 environment of abundant global liquidity. Spillovers seem to be strongest among the BRICS and in Latin America. These results are robust to various specifications of our models.
Keywords: F32; G15; F41; F42; 330; International topics; Econometric and statistical methods; Monetary policy framework; International financial markets; Financial system regulation and policies